Analisis Keuntungan Usaha Gula Kelapa Antara Pemilik Dan Penyewa Di Desa Durian Daun Dan Desa Sumber Rejo Kabupaten Bengkulu Utara - Puspita, Popi (Badan Penerbitan Fakultas Pertanian Universitas Ratu Samban, 2022)
The purpose of this study was to determine the profit of coconut sugar business between owners and tenants in farmer groups in Durian Daun Village and Sumber Rejo Village, North Bengkulu Regency. Determination of respondents and sampling in this study is by means of quota sampling, namely determining the nature of prospective respondents and determining the area of ​​observation, then the researcher or interviewer goes to the field to get respondents according to the criteria or characteristics that have been set. Researchers only took from two populations, namely in Durian Daun Village and Sumber Rejo Village, North Bengkulu Regency, as many as 26 respondents were then used as samples, so that the samples representing the coconut sugar business in Durian Daun Village and Sumber Rejo Village, North Bengkulu Regency were 26 people. The method used in this study is the totality approach, which is to determine the benefits of farming in Durian Daun Village and Sumber Rejo Village, North Bengkulu. The profit is obtained from total revenue/sales reduced by production costs. Furthermore, to find out the results of each total revenue and total cost. The results of this study are the production costs incurred by coconut sugar farmers in Durian Daun Village and Sumber Rejo Village consist of two sources of costs, namely fixed production costs in the form of premium costs, and variable costs which include raw material costs, labor and rental costs with a total The total production costs incurred by all coconut sugar farmers in Durian Daun Village and Sumber Rejo Village, which amount to 20 farmers are approximately IDR 3,028,000 and the total amount of coconut sugar production is 520 Kg. After knowing the amount of production costs incurred, another thing that needs to be known is the total income. The total income obtained by 20 respondents who are coconut sugar farmers in Durian Daun Village and Sumber Rejo Village totals approximately IDR 4,000,000. The profit obtained is by subtracting the total income from the total production costs, meaning Rp. 4,000,000 – Rp. 3,028,000 = Rp. 972,000.